OC-076 Extension of the Bowel Cancer Screening Programme to those aged 70–74 years, Torbay's experience. (23rd September 2015) - Feeney, M A; Beard, L; Bird, K; Williams, D C; Pullan, R D
Abstract : Introduction: The Bowel Cancer Screening Programme (BCSP) was launched in July 2006 to screen those aged 60–69 years. In September 2006 the South Devon Screening centre started screening and in September 2008 it was one of five sites to extend screening to those aged 70–74 years. This age group was not included in the pilot studies. This study has been undertaken to assess the uptake of the investigations in the over 70 s in the Torbay area (population 270 000). Methods: The data were collated by analysing central records of test kits sent out from our hub at Guildford and also our local prospective data set for all patients with positive faecal occult blood tests (FOBt). The first year of screening for each age group was analysed and compared, that is, for the 60–69 year old group, the data studied relate to the period 9/9/06 to 30/10/07. For the older age group (70–74 years) the study period was 9/9/08 to 30/10/09. Most subjects take a couple of weeks to return the kits so the study period was extended to allow for 12 months of colonoscopy data to be analysed. Results: In those over 70 years (compared to those 60–69 years) There is a very high rate of return of the FOBt kits (70% vs 59%) The FOBt +ve rate was much higher in this age (2% vs 1.1%) There was a lower rate of DNA at the nurse led clinic (0% vs 2%) Higher rate of informed dissent (ie, no further investigation chosen by the patient) (12% vs 2%) Slightly more patients were unfit for colonoscopy (2% vs 0.6%) There was a lower rate of colonoscopy (83% vs 92%) Colonoscopy completion rate was very similar (98.8% vs 99.3%) Colonoscopy findings in those over 70: Cancer rate 11% and polyp detection rate 34.5% which are in line with the incidence rates seen within the BCSP. Normal colonoscopies were recorded in 29%. Conclusion: In our population the rate uptake of the BCSP (returning FOBt) was higher in those over 70 years and they were twice as likely to have positive FOBt as the younger age group. Most of this older group was fit for colonoscopy and there was a significant yield of cancer and polyps. This study will help other screening centres to estimate the number of additional colonoscopies required to provide bowel screening for the extended age group up to 75 years. Bowel screening will be rolled out nationally to this age group during 2010.1